The Effect of Entrepreneurial Marketing on SME Business Performance: Moderated by Soft Lean Practices - Lisnawati Mantero; Murpin Joshua Sembiring; Tommy Christian Efrata (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In dynamic competition, SMEs need adaptive strategies such as entrepreneurial marketing and lean practices. This study examines the effect of entrepreneurial marketing and business performance by considering the role of soft lean practices and environmental turbulence as moderating variables. Using an explanatory quantitative methodology with a cross-sectional survey approach, this study involved 198 SMEs out of a total of 225 SMEs surveyed through purposive sampling. The theoretical framework of the study was built based on five theories: resource-based view theory, dynamic capabilities theory, contingency theory, entrepreneurship theory, and organizational learning theory. The results of the structural model analysis indicate that entrepreneurial marketing has a dominant positive influence (β = 0.782, t = 22.035, p < 0.001) on business performance. Soft lean practices show a substantial positive influence (β = 0.647, t = 7.216, p < 0.001), with a significant interaction effect (β = 0.213) between the two variables. The strong synergistic relationship (r = 0.866) confirms the importance of integrating these two practices. The evaluation of the model fit showed satisfactory results with SRMR values of 0.085 and NFI of 0.662. These findings contribute to the development of business strategies that integrate entrepreneurial marketing and soft lean practices.